2020
DOI: 10.1080/14686996.2020.1714476
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive modelling of hot deformation behaviour of a CoCrFeMnNi high-entropy alloy

Abstract: Models describing the constitutive flow behaviour of a metallic material are desired for appropriate process design and realization of defect-free components. In this study, constitutive equations based on the hyperbolic-sinusoidal Arrhenius-type model have been developed to define the hot deformation characteristics of a CoCrFeMnNi high-entropy alloy. The experimental true stress-true strain data were generated over a wide temperature (1023-1423 K) and strain rates (10 −3-10 s −1) ranges. The impact of strain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(21 citation statements)
references
References 48 publications
0
21
0
Order By: Relevance
“…By the Zener–Holloman parameter (Z), that is, the temperature-compensated strain rate, the relationship between the temperature and the strain rate corresponding to plastic deformation can be analyzed. According to Equation (1) [ 30 ], the respective constitutive equation can be expressed as follows: …”
Section: Resultsmentioning
confidence: 99%
“…By the Zener–Holloman parameter (Z), that is, the temperature-compensated strain rate, the relationship between the temperature and the strain rate corresponding to plastic deformation can be analyzed. According to Equation (1) [ 30 ], the respective constitutive equation can be expressed as follows: …”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the apparent activation energy for the hot-deformation of the Co 35 Cr 25 Ni 15 Mn 15 Fe 10 TRIP-HEA was 385.7 kJ/mol, which is slightly higher than that of the Cantor HEA (~350 kJ/mol) [ 17 , 18 , 19 , 20 ]. The activation energies of pure aluminum, copper, and nickel are 142, 197, and 285 kJ/mol, respectively [ 24 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the recrystallized grains did not exhibit a strong texture. The apparent activation energy of the Cantor HEA is approximately 350 mJ/mol [ 17 , 18 , 19 , 20 ], which is close to that of the diffusion of Ni in the system [ 23 , 24 , 25 ]. The steady-state deformation is controlled by the dislocation climb [ 25 ].…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…It was reported that discontinuous dynamic recrystallization (dDRX) notably contributed to grain refinement during hot-deformation, in which the recrystallized grains tend to nucleate at the primary grain boundaries (GBs) [14,24]. The apparent activation energy of the Cantor HEA is close to that of the diffusion of Ni in the alloy, and the dislocation climb determines the steady-state deformation [25][26][27][28][29][30][31][32]. Even though the DRX behaviors of CoCrNi MEA and the novel Co-rich TRIP HEA were investigated in our previous studies [14,24], the influence of interstitial atoms such as C and N on hot-deformation and grain structure evolution have not been clarified.…”
Section: Introductionmentioning
confidence: 99%